Pengaruh Jarak Elektroda dan Tegangan terhadap Efektivitas Pengolahan Air Lindi dengan Metode Elektrokoagulasi-Adsorpsi Zeolit - Fadhila, Anisa Nur; Purnama, Herry (Jurnal Teknik Kimia USU, 2022)
The problem that has been difficult to overcome until now is the waste problem. Landfilling remains a method that is often used but has a disadvantage in the form of leachate production. Leachate or leachate is defined as wastewater produced from Final Disposal Sites (TPA). The combination of electrocoagulation and adsorption methods can be a promising treatment technology. The electrocoagulation process was carried out for 1 hour using iron electrodes. The variations used are electrode distances consisting of 1 cm, 1.5 cm, and 2 cm while the voltages consist of 10 volts, 20 volts, and 30 volts. In adsorption, zeolite adsorbent was used with a residence time of 2 hours. The research stages started from the preparation of leachate samples, examination of initial characteristics, leachate treatment, and testing of COD, TSS, and pH. The results showed that the optimal variation was obtained at a distance of 1 cm and a voltage of 30 volts with a COD efficiency of 98.84% and TSS of 99.82%. For the pH value, the result is that the greater the distance between the electrodes and the voltage, the higher the pH value obtained.